Effects of bacterial strains on undrained cyclic behavior of bio-cemented sand considering wetting and drying cycles - Nilanjana Banik; Rajib Sarkar (Journal of Rock Mechanics and Geotechnical Engineering)
The microbial-induced calcite precipitation (MICP) technique has been developed as a sustainable methodology for the improvement of the engineering characteristics of sandy soils. However, the efficiency of MICP-treated sand has not been well established in the literature considering cyclic loading under undrained conditions. Furthermore, the efficacy of different bacterial strains in enhancing the cyclic properties of MICP-treated sand has not been sufficiently documented. Moreover, the effect of wetting-drying (WD) cycles on the cyclic characteristics of MICP-treated sand is not readily available, which may contribute to the limited adoption of MICP treatment in field applications. In this study, strain-controlled consolidated undrained (CU) cyclic triaxial testing was conducted to evaluate the effects of MICP treatment on standard Ennore sand from India with two bacterial strains: Sporosarcina pasteurii and Bacillus subtilis. The treatment durations of 7 d and 14 d were considered, with an interval of 12 h between treatments. The cyclic characteristics, such as the shear modulus and damping ratio, of the MICP-treated sand with the different bacterial strains have been estimated and compared. Furthermore, the effect of WD cycles on the cyclic characteristics of MICP-treated sand has been evaluated considering 5–15 cycles and aging of samples up to three months. The findings of this study may be helpful in assessing the cyclic characteristics of MICP-treated sand, considering the influence of different bacterial strains, treatment duration, and WD cycles.